Food waste in the United States: A contributing factor toward environmental instability - Hickey, Michael E.; Ozbay, Gulnihal (Frontiers in Environmental Science, 2014)
The world’s population continues to increase at record rates along with corresponding nutritional needs and related agricultural consequences. In the United States, food waste levels serve as dominant components of land-fill masses, oil and freshwater waste, methane and CO2 emissions, damage to wildlife ecosystems, and substantial financial losses. Agricultural effects on the environment were investigated through various research studies, referenced in this document, and efforts made toward food waste recycling were discussed as noteworthy models concerning improvements in sustainable agricultural practices. Food waste levels in the United States can be traced as faults of consumers, agricultural businesses, as well as federal legislation and there is an evident need for reform to maintain consumer health, viable foreign affairs, and environmental sustainability. Present agricultural practices are intense and rapid, increasing the risk of soil infertility and commercial alterations in production yields; repercussions well documented in neighboring nations. Experts argue that food waste in developed countries damages food availability around the world and, based on current agricultural practices and production, there is debate conc